KAJIAN KINERJA LAYANAN SANITASI DI KOTA SEMARANG - Artiningsih Artiningsih; Fadjar Hari Mardiansjah; Nafisah Anas; Megy Utya Khairunisa (Jurnal Riptek, 2018)
As a centre of settlement and distribution of government services, social and economic, Semarang attract the residents from outside the urban area to do a migration. This has led to an increase in the growth of the urban population as well as various urban problems, such as the low quality of public service facilities and the emergence of the informal sector and slum settlements. In slum area, there is an inadequate sanitation, poor hygiene practices, excessive population density, and contaminated water that have potential to create unhealthy conditions. The purpose of this study is to assessthe performance of sanitation services in Semarang. The research method is scoring analysis techniques supported by Geographic Information System as a sculling up method based on sanitation indicators withdrawn from a case study in Bullu Lor Sub district. The results of the study revealed that Semarang has 3 typesof sanitation performance, namely under standard (basic need), with standard and beyond standard. However, Semarang need a policy framework which determine a mile stone of sanitation services improvement achievements. Education through either enhancement on community awareness, lesson learned from sanitation services improvement in public facility orsanitation governance base on community empowerment become effective corrective actions.